2014
DOI: 10.1176/appi.ps.201200561
|View full text |Cite
|
Sign up to set email alerts
|

Public Stigma and Self-Stigma: Differential Association With Attitudes Toward Formal and Informal Help Seeking

Abstract: Anticipated self-stigma and perceived public stigma appeared to have a differential impact on attitudes toward formal and informal help seeking. Internalization of negative stereotypes was negatively associated with the perceived importance of care from medical providers (general practitioners and psychiatrists). Awareness of stereotypes held by others deterred respondents from acknowledging the importance of informal care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
110
1
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(127 citation statements)
references
References 73 publications
4
110
1
12
Order By: Relevance
“…An important linkage between stigma and suicide is suggested to be "help seeking" (Reynders et al, 2014); help seeking for psychological problems is suggested as protecting people from suicide. Because people with a higher level of internalized stigma consider help from medical care providers as less important (Pattyn et al, 2014), they may not seek help when encountering psychological problems, and this might lead to suicidal behavior. However, despite the support for hypotheses from our cross-sectional study, more evidence, especially from longitudinal studies, is required to confirm them.…”
Section: Discussionmentioning
confidence: 99%
“…An important linkage between stigma and suicide is suggested to be "help seeking" (Reynders et al, 2014); help seeking for psychological problems is suggested as protecting people from suicide. Because people with a higher level of internalized stigma consider help from medical care providers as less important (Pattyn et al, 2014), they may not seek help when encountering psychological problems, and this might lead to suicidal behavior. However, despite the support for hypotheses from our cross-sectional study, more evidence, especially from longitudinal studies, is required to confirm them.…”
Section: Discussionmentioning
confidence: 99%
“…Vogel, Wade, and Haake (2006) defined self-stigma as: "the reduction of an individual's self-esteem or self-worth caused by the individual self-labeling herself or himself as someone who is socially unacceptable" (p. 325). Self-stigma is associated with self-esteem, self-efficacy, and help-seeking behaviors (Corrigan, Larson, & Rusch, 2009;Pattyn, Verhaeghe, Sercu, & Bracke, 2014). For instance, Pattyn and colleagues (2014) found that internalized societal stigma was negatively related to conceptualizations of medical care as important.…”
Section: Self-stigmamentioning
confidence: 99%
“…The influence of the community might also be explained by a higher level of anticipated self-stigma. Research has shown that seeking help from general practitioners and psychiatrists, but not from psychologists, is more difficult when self-stigma is more pronounced (Pattyn, Verhaeghe, Sercu, & Bracke, 2014). It also seems to be the case that hospitalization is linked with higher self-stigma (Sarıkoç & Öz, 2016).…”
Section: Ontological Aspectsmentioning
confidence: 99%
“…On the other hand, the fear that the community would gossip can be associated with a higher level of perceived public stigma. In that case, one is afraid of devaluation and social Diasporic Muslims, Mental Health, and Subjectivity discrimination by one's social network (Ciftci, Jones, & Corrigan, 2013;Pattyn et al, 2014). This is also the reason why many persons with mental health problems are reluctant to seek treatment (Sarıkoç & Öz, 2016).…”
Section: Ontological Aspectsmentioning
confidence: 99%